The Principle of Presumption of Innocence: Ensuring Suspect Rights During the Investigation Process - Suhendar, Suhendar; Candra, Septa (JURNAL AKTA, 2025)
This study aims to determine the implementation of the suspect's rights as a manifestation of the presumption of innocence at the investigation level. To identify the obstacles to implementing the suspect's rights during the examination process at the investigative level. The type of research used is a normative research type, based on the results of the research conducted, in the implementation of the suspect's rights in the examination process regardless of whether it is proven or not, the suspect is still protected by various rights protections including the right to be examined immediately, the right to provide information freely or in a very simple sense during the examination there is no pressure or physical violence during the examination, but there is still one right that is not by the suspect's rights regulated in the Criminal Procedure Code, namely the suspect does not receive legal assistance. In the implementation of the suspect's rights, there are several obstacles, including the unprofessionalism of investigators in conducting investigations, the behavior and actions of law enforcement officers due to the suspect's ignorance or lack of understanding of the rights that should be obtained as a suspect, and suspects who do not understand the importance of legal assistance, dishonesty and transparency of suspects in the integration process (examination), and uncooperative suspects usually act passively and are silent.